Pregabalin effects on neural response to emotional faces - Aupperle, Robin L.; Tankersley, Dharol; Ravindran, Lakshmi N.; Flagan, Taru; Stein, Nathan R.; Stein, Murray B.; Paulus, Martin P. (Frontiers in Human Neuroscience, 2012)
Pregabalin has shown promise in the treatment of anxiety disorders. Previous functional magnetic resonance imaging (fMRI) studies indicate agents used to treat anxiety, e.g. SSRIs and benzodiazepines, attenuate amygdala, insula, and medial prefrontal cortex (PFC) activation during emotional processing. Our prior study has shown that during anticipation of an emotional stimulus, pregabalin attenuates amygdala and insula activation but increases medial PFC activation. In this study, we examined whether, similar to SSRIs and benzodiazepines, pregabalin attenuates amygdala, insula and medial PFC during emotional face processing. Sixteen healthy volunteers underwent a double-blind within-subjects fMRI study investigating effects of placebo, 50 mg, and 200 mg pregabalin on neural activation during an emotional face-matching task. Linear mixed model analysis revealed that pregabalin dose-dependently attenuated left amygdala activation during fearful face-matching and left anterior insula activation during angry face-matching. The 50 mg dose exhibited more robust effects than the 200 mg dose in the right anterior insula and ventral ACC. Thus, pregabalin shares some similarity to SSRIs and benzodiazepines in attenuating anger and fear related insula and amygdala activation during emotional face processing. However there is evidence that a subclinical 50 mg dose of pregabalin produced more robust and widespread effects on neural responses in this paradigm than the more clinically-relevant 200 mg dose. Taken together, pregabalin has a slightly different effect on brain activation as it relates to anticipation and emotional face processing, which may account for its unique characteristic as an agent for the treatment of anxiety disorders.